PEMBINAAN KEPATUHAN PERPAJAKAN USAHA MIKRO, KECIL DAN MENENGAH KOTA DEPOK MELALUI WORKSHOP PENGISIAN SURAT PEMBERITAHUAN PAJAK PENGHASILAN - Selvi .; Indra Sumarna; Alief Ramdhan (Institut Ilmu Sosial dan Manajemen Stiami, 2021)
The reduction of tax rates for Micro, Small and Medium Enterprises (MSMEs) is actually to provide convenience to business actors in exercising their tax rights and obligations. However, the preliminary survey conducted by researchers shows that there are still many business actors who do not carry out tax obligations because of their ignorance of taxation. Therefore, the development of tax compliance for MSME actors begins with providing workshops on filling out Income Tax Returns to 20 MSMEs in Depok City by the collaboration with the Department of Cooperatives, Small Medium Enterprises and Market of Depok. The method is carried out by giving lectures, demonstrations, income tax calculation exercises and filling of Income Tax Return. The results of the implementation show that as many as 18 MSMEs can calculate up to filling in Income Tax Return